The potential use of organosilane water soluble nanomaterials as water vapor diffusion retarders for wood - Gholamiyan, Hadi; Tarmian, Asghar; Doost Hosseini, Kazem; Azadfallah, Mohammad (Maderas. Ciencia y Tecnología, 2025)
The retarding effect of organosilane water soluble nanomaterials (nano-zycosil and nano-zycofil) on water vapor diffusion through poplar wood (P.nigra) was evaluated in comparison with that of clear coatings (sealer and nitrocellulose lacquer and polyester lacquer) using cup and sorption methods. Two drying methods were applied to dry the nanomaterials -coated substrates: oven drying at temperature of 103 ± 2 °C for 24 h. and climatically drying at temperature of 25 °C and relative humidity of 65% for 20 minutes. The results showed that both coating materials decreased the water vapor diffusion rate through the wood. The sealer and nitrocellulose lacquer coating represented a stronger effect on the diffusion coefficient of wood compared to the other coatings. In this case, the nano-zycosil represented a better performance compared to the nano-zycofil. Furthermore, the drying method of the nanomaterials -coated substrates can impact the nanomaterials performance. The water vapor diffusion through the oven-dried substrates was faster than that through the climatically dried ones.